The Social Impact of the Covid-19 Pandemic on Communities Around Mangrove Tourism in Bintan Regency, Riau Islands Province - Angga Reni; Khairunnisa; Tetty (Agrikan: Jurnal Agribisnis Perikanan, 2022)
The Corona Virus Disease 2019 (Covid-19) has been confirmed as pandemic by WHO. Every Country in the world is affected by this disease, including Indonesia. Covid-19 impacts not only public health but also other sectors such as tourism. This study aims to determine the social impact of Covid-19 on the community around mangrove tourism in Bintan Regency which was held from July to November 2022 in Bintan Regency. The analysis used is quantitative descriptive using a Likert scale analysis with attributes in the form of: (1) habits; (2) attitude; and (3) social norms. The results of the study show that there are habits of people who tend to be more aware of the importance of maintaining cleanliness and health. Furthermore, there has also been a change in attitude in the form of a tendency for society to be more careful of new people and to be more introverted. Then changes in norms that developed in society took the form of questioning the timing of activities, making it difficult for guests at gatherings, and increasingly strict reporting of arriving guests.